CORRELATION OF ACADEMIC AND LABOUR VARIABLES OF GRADUATES OF ACCOUNTING SCIENCE OF UNMSM - Gutiérrez Huby, Ana María (2012)
The analysis presented in this article , focusing quantitative , is descriptive -explanatory analyzing the relationship between variables in levels satisfaction of the graduates of the Faculty Accounting Sciences of our University - From sex and experience regarding labor - professional training , performance and current working conditions. When it was applied statistical independence test Chi - Square, which allowed testing of the assumptions made . The data were collected through a ' Graduate Survey " administered by the School Academic and Professional Accounting in the year 2012 , a period in which have registered three groups of respondents making a population of 203 graduates. A generic way is concluded that the presence of women in the accounting career is higher ( 65 %) compared to males ( 35%) and that the rate of employability of graduates (91% ) is quite high.